HARAPAN KINERJA DAN HARAPAN USAHA GURU DALAM MENGGUNAKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DENGAN PENDEKATAN UNIFIED THEORY OF ACCEPTANCE AND USE OF THECHNOLOGY DI SD NEGERI 28/IV KOTA JAMBI - Putri, Adella Rahmadi; Sofwan, Muhammad (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to describe teachers' performance expectations and effort expectations in using Information and Communication Technology (ICT) through the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. The research was conducted at Sekolah Dasar Negeri 28/IV Kota Jambi trough qualitative research with a case study design. Data were collected through observations and interviews with teachers at SDN 28/IV Kota Jambi. Data analysis was conducted through the Miles and Huberman model. The results indicate that two components of the UTAUT model, performance expectations and effort expectations, were achieved by the teachers in the learning process through ICT. The performance expectations aspect showed that ICT use in the learning process provided benefits, helped achieve learning objectives, made teachers more productive, innovative and creative, and enhanced collaboration among teachers. Meanwhile, the effort expectations aspect demonstrated that ICT use made it easier for teachers to conduct lessons, design learning tools, and made learning more effective, efficient, clearer, and easier to be understood.